2023
DOI: 10.1097/qad.0000000000003696
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of yellow fever vaccine in people with HIV

Edwiges Motta,
Luiz Antonio B. Camacho,
Marcelo Cunha
et al.

Abstract: Objective: To evaluate immunogenicity and reactogenicity of Yellow Fever (YF) vaccine in people living with HIV (PLWH) compared to HIV-uninfected controls. Design: In this longitudinal interventional trial (NCT03132311), PLWH with CD4 ≥200 cells/μL and controls, aged 18–59, without a previous history of YF vaccination received a single standard dose of YF vaccine (17DD) and were followed at Days 5, 30 and Year 1. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…We showed recently that the 17DD vaccine was safe and well tolerated in PLWH. 20 However, we found that 17DD viremia was associated with adverse events in PLWH and HIV-uninfected controls (HIV(-) controls). 20 In this study, we aimed to further explore factors associated with the occurrence of 17DD viremia in PLWH and HIV(-) controls.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…We showed recently that the 17DD vaccine was safe and well tolerated in PLWH. 20 However, we found that 17DD viremia was associated with adverse events in PLWH and HIV-uninfected controls (HIV(-) controls). 20 In this study, we aimed to further explore factors associated with the occurrence of 17DD viremia in PLWH and HIV(-) controls.…”
Section: Introductionmentioning
confidence: 76%
“… 20 However, we found that 17DD viremia was associated with adverse events in PLWH and HIV-uninfected controls (HIV(-) controls). 20 In this study, we aimed to further explore factors associated with the occurrence of 17DD viremia in PLWH and HIV(-) controls. In addition, we describe the kinetics of hematological and liver laboratorial parameters and assess whether 17DD viremia and HIV status were associated with the occurrence of laboratorial abnormalities.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…For PLWH, safety and immunogenicity reports are mostly limited to small observational studies and case reports [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], except for a few cohort studies [ 16 , 17 , 18 , 19 , 20 , 21 ], and indicate that markers of HIV disease progression are associated with a lower level and shorter persistence of YF neutralization antibody (NAb) titers [ 11 , 17 , 18 , 20 ]. To address this, a longitudinal prospective non-randomized interventional trial with 280 PLWH was conducted and confirmed the safety of the YF vaccine in PLWH with CD4 + cell count ≥200 cells/mm 3 [ 22 ]. However, immunogenicity was impaired in PLWH, particularly in those with a high viral load, low CD4 + T cell count, and low CD4/CD8 ratio at vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the mechanisms that could impair YF vaccine immunogenicity in PLWH, our study evaluated the pre-vaccination frequencies of several cellular subsets and inflammation markers that are affected by HIV infection in a longitudinal interventional trial that evaluated the immunogenicity and reactogenicity of the YF vaccine in PLWH and HIV-negative controls [ 22 ].…”
Section: Introductionmentioning
confidence: 99%